Antimicrobial Potential of Streptomyces ansochromogenes (PB3) Isolated From a Plant Native to the Amazon Against Pseudomonas aeruginosa - Amorim, Erika Alves da Fonseca; Castro, Erima Joussiely Mendonça; Souza, Silva Viviane da; Alves, Mateus Silva; Dias, Léo Ruben Lopes; Melo, Maycon Henrique Franzoi; da Silva, Ilana Mirian Almeida; Villis, Paulo Cesar Mendes; Bonfim, Maria Rosa Quaresma; Falcai, Angela; Silva, Maria Raimunda Chagas; Monteiro-Neto, Valério; et al. (Frontiers in Microbiology, 2020)
The objective of this study was to evaluate the antibacterial action of filamentous bacteria isolated from the Byrsonima crassifolia leaf. An endophytic bacterium was classically and molecularly identified as Streptomyces anschromogenes. Screening for antibacterial action against pathogens with medical relevance (Klebsiella pneumoniae ATCC 0023, P. aeruginosa ATCC 0030, Staphylococcus aureus ATCC 6538, Corynebacterium diphteriae ATCC 27012, Mycobacterium abscessus massilienseGo01, Cryptococcus gattii ATCC 24065, and Cryptococcus neofarmans ATCC 24067) demonstrated activity against the bacterium Pseudomonas aeruginosa ATCC 0030 with inhibition diameter zones (IDZ) of 17.6 ± 0.25 mm in the preliminary screening in solid medium. After fermentation in liquid medium, an IDZ of 19.6 ± 0.46 mm and a minimum inhibitory concentration (MIC) of 0.5 mg/mL were detected. The extract was also Sub-MIC The antibiofilm action was observed with 100% inhibition of biofilm formation at a concentration of 0.250 mg/mL. When the infection curve was prepared, it was observed that the metabolite was effective in protecting the larvae of Tenebrio molitor. Therefore, it can be concluded that the metabolite produced by the endophytic bacterium Streptomyces sp. is promising for future use as an alternative strategy against bacterial resistance.